Monitoring Tetesan Cairan Infus Berbasis IoT - Yadnya, Made Sutha; Larasati, Alfiyyah Reghin; Muljono, Agung Budi; Budiman, Djulfikry (LPPM Universitas Mataram, 2025)
The need for proper and accurate medical equipment not limited by distance and time is to make monitoring of system. One part is that in patient care is to accurately monitor the flow of infusion fluids according to the fluid that comes out of the infusion in the right dose so that it can avoid complications that occur in patients. The creation of this system is to develop a manual observation system to be based on IoT (Internet of Things) with the advantages of remote monitoring of the flow of infusion fluids and being able to provide information in real time. The use of an internet network with a system of equipment has sensors to detect the weight of the infusion fluid, microcontrollers, and IoT communication modules connected to android. Â